Analisis Klaster Hierarki untuk Pengelompokkan Kabupaten/Kota di Jawa Tengah Berdasarkan Indikator Indeks Pembangunan Manusia (IPM) Tahun 2015 - Putri, Riyana; Widodo, Edy (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 1 No 1 (2017): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami ), 2017)
Central Java is administratively divided into 29 Districts and 6 Cities. The large number of Districts/ cities will certainly provide a depiction of HDI varied. Therefore, it is necessary to classify districts/cities based on HDI by using cluster analysis. The cluster analysis used by the researcher is the Hierarchy method with five combined methods, namely Single Lingkage, Average Lingkage, Complete Lingkage, Centroid, and Ward's methods. In this research used data of 35 Districts /cities in Central Java. The validity index used to determine the optimum number of groups is RMSSTD (Root Mean Square Standard Deviation). The smallest RMSSTD Index of 170,851 is the Average Lingkage, Complete Lingkage and Ward method with 4 groups. Group 1 consists of 19 Districts/cities, group 2 consists of 3 Districts/cities, group 3 consists of 10 Districts/cities and group 4 consists of 3 Districts /cities with the specified variables. In cluster 2 has a level characteristic Life Expectancy (Eo), Mean Years of Schooling (MYS), Purchasing power parity (PPP) which is when compared to other groups. So, it can be concluded that cluster 2 which consists of Wonosobo Districts, Tegal Districts, and Brebes Districts need to get help from the government.